Comparison of the Menstrual Cycle in Undernoted and Over Nutrited Adolescents at SMA Negeri 1 Pinolosian - Sunarto Kadir; Niluh Arwati; Della Fatimi Modeong (Journal of Health, Technology and Science (JHTS), 2022)
This study aims to determine the comparison of menstrual cycles in undernourished and overweight adolescents at SMA Negeri 1 Pinolosian. This research method uses an observational research design with a cross- sectional approach. The population of this study was 128 female students. The sample used was 95 respondents using a purposive sampling technique. Using data analysis techniques, namely Univariate analysis with frequency distribution tables and Bivariate with Chi-Square test P = <0.05. The results showed that there were 46 (36%) undernutrition and 49 (38.2%) over nutrition. Normal menstrual cycles for undernourishment 31 (63.3%) and for over nutrition 26 (56.6%), while undernourished those with abnormal menstrual cycles 18 (36.8%) and over nutrition 20 (43.3%). A good diet with poor nutrition 27 (58.7%), and not good 19 (41.3%). While a good diet on excess nutrition 25 (51%) and not good 24 (49%). And the results of the Chi Square test of normal and abnormal menstrual cycles in undernourished and overweight adolescents with a P value = 0.00 There is a comparison of the menstrual cycle in undernourished and overweight adolescents. It is recommended for female students to pay attention to diet properly in order to get good nutritional status so that it can also have a good impact on the menstrual cycle.